Moral Identity and Electronic Aggression on Instagram Users: Self-control as a Moderating Variable - Rahman, Agus Abdul (Universitas Muhammadiyah Surakarta, 2023)
Abstract. Electronic aggression has become a growing phenomenon with the advent of social media platforms, including Instagram. Instagram's characteristics include easy access and the ability to speed up communication and information dissemination, which leads to electronic aggression. This phenomenon is highly concerning. One of the factors that may help Instagram users avoid electronic aggression is the internalization of moral values. However, moral values are not always realized in every context of life. As a result, other factors that can strengthen Instagram users' control over electronic aggression are required. This can be achieved, for example, through good self-control ability. The purpose of this research is to investigate the effect of moral identity on electronic aggression using self-control as a moderating variable. The research used a correlational design, involving 250 Instagram users as respondents. Data were collected using a moral identity questionnaire scale developed by Black and Reynolds; a self-control scale by Tangney, Baumeister, and Boone; and an electronic aggression scale by Bennett, Guran, Ramos, and Margolin. The findings of the research indicate that moral identity and self-control have a negative impact on electronic aggression among Instagram users. Furthermore, self-control ability can increase the effect of moral identity on electronic aggression by 10.7%.Keywords: Moral identity; self-control; electronic aggression; Instagram users.